The issues and challenges in implementing system integration in non-IT public hospitals: a case study in Tengku Ampuan Rahimah Hospital Klang / Shazalienna Saharudin - Saharudin, Shazalienna (2012)
System integration is required to operate across the Internet or Local Area Network (LAN) and across different domain to support for processes, resources and users. The system integration between relevant departments onto a single computer system that can serve all those different departments' particular needs is complex and these requirements lead to a number of challenges. This report will concentrate on issues and major challenges for which we claim there is no easy solution. These challenges originate from the fact that users and system are becoming increasingly integrated and are effectively leading us to large-scale socio-technical distributed system. The design of integrated system is a challenge when it involves employees as a requirement to proper operation of the system as a whole. The successful implementation of system integration in healthcare does not only depend on technical issues but also acceptability and acceptance issues. The organisation will not gain any benefit unless the integration works are implemented successfully. This report adopts Technology Acceptance Model (TAM) to identify the acceptance from the end users in adopting new technology. TAM specifies the causal relationships between system design features, perceived usefulness, perceived ease of use, attitude toward using and actual usage behaviour. Focus group interviews with end users were done guided by questionnaire. The results of the interviews were categorized into few themes namely overall acceptance, usefulness, usability and behavioural intention.